The Investigation of Relationship between Earnings Quality and Future Stock Returns in Tehran Stock Exchange (TSE) - Hamid Haghighat (Shahid Bahonar University of Kerman, 2011)
This research investigates the relationship between quality of earnings and future stock returns in the selected firms totally, and in the firms in separate categories with various degrees of earnings quality, by choosing the accruals as the representative of earnings quality for the firms listed in the Tehran Stock Exchange (TSE). In this study the size and growth of firms are taken as the control variables. In hypothesis testing, the accruals and their components in arbitrary and non-arbitrary values are used as independent variables, and the future stock returns are taken as dependent. Using data from 91 firms in period 1375-1386, and the method of regression with cross-section series data, the results indicate that in the totally assessment, except for some cases in the medium and low degrees of earnings quality, the future stock returns are not affected by the earnings quality. Accruals components were also examined for which similar results were found. When the firms were categorized into three segments based on the degree of earnings quality, separate hypothesis tests indicate significant relationship between future stock returns and earnings quality.